TERBENTUKNYA BUMI DAN HANCURNYA BUMI (AGAMA BUDDHA MEMBERIKAN JAWABAN SEIRING DENGAN PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI) - Manggala Wiriya Tantra Tantra (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2020)
Natural disasters that often occur after the 20th century lead many people to assume that the earth will soon experience destruction. Buddhism knows the process of the destruction of the earth contained in the Satta Suriya Sutta, Anguttara Nikaya, which explains the earth to collapse after the seventh sun appeared. However, that does not mean if the earth is destroyed then there is no more life. In Ananda Vagga, Anguttara Nikaya, the Buddha explains that there are more than one billion solar systems in the universe. The development of science and technology which is progressing very rapidly, has found many planets that can be inhabited by living things and some stars are also found in this galaxy. This shows the equivalence between Buddhism and the development of science and technology. The condition of the earth is greatly influenced by human behavior, if human morals degenerate the earth will experience more rapid destruction, on the contrary if human morals get better the earth will be sustainable, so the core of the explanation contained in Pattakammavagga, Anguttara Nikaya. The best solution given by Buddhism in overcoming the destruction of the earth is to eliminate the kilesa (defilement), that is, all the elements of lobha (greed), the element of sin (hatred), and the element of moha (ignorance) in humans. Self-control is the first step to extinguish the kilesas. If all three have been eroded away, the moral quality must be good and the earth more sustainable.